New work on the first decade of higher medical education in Irkutsk - L. V. Rychkova; V. A. Shalamov (Acta Biomedica Scientifica, 2025)
This publication reviews a new study by A.V. Shcherbatykh and E.S. Filippov “At the origins of Irkutsk State Medical University (1919–1930)”. A review of the authors’ previous experience demonstrates that the book was the result of many years of effort to collect and systematize historical documents and materials. Seventy six archival files, periodicals, photographs and over 200 scientific publications were used as sources. The text of the work has a complex, branched structure. The principle of consistency is implemented by including the university in the panorama of the era. The materials concerning the establishment of the university in Irkutsk and its Faculty of Medicine are systematized. A significant amount is devoted to the characteristics of the founders of the Irkutsk Medical School. Attention is paid to the formation of educational and clinical bases of the Faculty of Medicine, as well as the organization of clinical education within its walls. The authors did not ignore the educational and scientific activities of medical specialists at the university. Information is also provided on the first (1922) and subsequent (1923–1930) graduates of the Faculty of Medicine. The author’s chronicle of the development of the Medical Faculty of Irkutsk State University completes the structure. The book contains 170 scanned documents, 132 photographs, 42 tables, 24 biographies and 2 maps, which allow us to fully reveal the circumstances of the first decade of higher medical education in Eastern Siberia. The analysis of the text of the work showed its non-standard construction. It combines scientific research, documentary narration and chronicling of events. The publication should be classified as a chronicle-documentary study.